The Impact of Guided Discovery Learning Method with Character Education and Competitiveness toward Students Scientific Essay Writing Skills (Pengaruh Metode Discovery Learning Bermuatan Pendidikan Karakter dan Berdaya Saing terhadap Keterampilan Menulis) - Yunisa Oktavia; Alpino Susanto; Atmazaki Atmazaki; Mafardi Mafardi; Arif Setiawan; Rahayu Fitri; Siti Marpuah (Universitas PGRI Sumatera Barat, 2023)
The study starts by acknowledging the challenge of students' restricted capacity to properly grasp scientific essays. The acquisition of knowledge pertaining to the rules of composing scientific essays, alongside a comprehensive understanding of the intricacies of bahasa course, has significant importance for students. The present investigation adopts a quantitative methodology and utilizes experimental techniques. The participants of this study were students who were currently enrolled in the engineering study program at UMRAH during the initial semester of the academic year 2018-2019. The objective of this study is to provide a comprehensive description of the influence exerted by the guided discovery learning strategy, in conjunction with character education and competition, on the enhancement of students' proficiency in scientific essay writing. Various methodologies, including statistical tests and survey questionnaires, are frequently employed in data analysis techniques that are prevalent in research investigations. Throughout the lecturer's presentation of educational material, students exhibit passion and courtesy in their reciprocal replies, so reflecting their familiarity with the instructional methodology being discussed. This study use character education as a means of developing students' cognitive and behavioral qualities, hence nurturing a mentality oriented towards competition. The results of the study indicate that the integration of the discovery learning method with character education and competition had a noteworthy influence on students' competence in scientific essay composition. The obtained value of 5.739, which surpasses the crucial value of 1.688 at a significance level of 0.05 and with 36 degrees of freedom (df), provides evidence in favor of this assertion. Given that the calculated t-value exceeds the crucial t-value, it is appropriate to accept the null hypothesis (H0). The findings of this study carry substantial significance for the progress of educational science, perhaps yielding benefits for the discipline. Moreover, this study might serve as a valuable resource for informing the adoption and integration of various pedagogical approaches